ˆ†BLEU: A Discriminative Metric for Generation Tasks with Intrinsically Diverse Targets - Galley, Michel; Brockett, Chris; Sordoni, Alessandro; Ji, Yangfeng; Auli, Michael; Quirk, Chris; Mitchell, Margaret; Gao, Jianfeng; Dolan, Bill (Proc. of ACL, 2015)
We introduce Discriminative BLEU (∆BLEU), a novel metric for intrinsic evaluation of generated text in tasks that admit a diverse range of possible outputs. Reference strings are scored for quality by human raters on a scale of [−1, +1] to weight multi-reference BLEU. In tasks involving generation of conversational responses, ∆BLEU correlates reasonably with human judgments and outperforms sentence-level and IBM BLEU in terms of both Spearman’s ρ and Kendall’s τ.